Leveraging Promotion Mix Strategies to Enhance Lombok's Tourism: A Case Study of Look Lombok Tour & Travel - Surayyal Hizmi; Aura Milinia Amanda; Farid Said; Nawawi (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
Despite the significant tourism potential and government initiatives in Indonesia, the popularity of Lombok Island remains below expectations, particularly exacerbated by the COVID-19 pandemic. Look Lombok Tour & Travel, a local travel agency, faces substantial challenges in attracting tourists. This study aims to identify the most effective promotional strategies for Look Lombok Tour & Travel's tour packages by applying the Promotion Mix Framework. We collected data from previous annual reports and conducted interviews with three key staff members using a qualitative descriptive methodology, which we then analyzed to identify the strengths and weaknesses of the promotional efforts. The results demonstrate that Look Lombok Tour & Travel employs a comprehensive array of promotional strategies—advertising, public relations, direct marketing, sales promotion, and personal selling—to effectively reach diverse demographics and align with current industry trends. Despite these strategic efforts, the study identifies critical areas needing improvement, including the development of distinctive tour packages, addressing budget limitations, fostering innovation, integrating advanced technologies, and establishing robust evaluation mechanisms. To overcome these challenges and enhance promotional efficacy, the study recommends investing in innovative technology-driven tactics and conducting regular strategic evaluations. These initiatives are anticipated to significantly enhance Lombok's appeal as a tourist destination, ensuring sustainable growth and resilience in its tourism industry.